Extraction of volatile fatty acids from leachate via liquid- liquid extraction and adsorption method - Razali, Yasmin Syafikah; Tajarudin, Husnul Azan; Daud, Zawawi (UTHM Publisher, 2018)
Volatile fatty acids (VFAs) are used in wide range of commercially-important chemicals. Treatment of leachate at landfills by fermentation process will produce VFAs (butyric acid, acetic acid, propionic acid, isovaleric acid and isobutyric acid) can be considered as a replacement for petroleum-based VFA due to their degradability, renewability and sustainability. Therefore, separation of VFAs residue after the leachate treatment is important and essential from the point of view of pollution control and recovery of useful material. The aim of this study is to compare the percentage of VFAs extracted between liquid-liquid extraction and adsorption method. The VFAs extracted in this study were acetic and butyric acids produced from the fermentation of leachate using Clostridium butyricum. Response surface methodology (RSM) was used using central composite design (CCD) to optimize the parameters that affect the extraction of acetic and butyric acids. Liquid-liquid extraction using petroleum ether (69/80) with optimum parameters (temperature: 35 oC, pH: 4.8, agitation: 175.4 rpm, incubation time: 16.8 h and volume of treated leachate: 14.1 %) showed that the acetic acid and butyric acid extracted were 28.1% and 88.8% respectively. On the other hand, adsorption method using activated carbon showed the highest extraction percentage of acetic acid, 87.4% and butyric acid 94.1% with the optimum parameters of pH 3.0, 19.8 % activated carbon weight, 40 oC, 9.5 h incubation time and 179.9 rpm agitation speed.